(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2026)
The following literature review analyzes theoretical approaches that explain the role of oral transmission in the preservation of traditional musical practices, with an emphasis on the Chirimía Caucana. Based on a systematic analysis of recently indexed sources, it was identified that orality constitutes a central mechanism for the intergenerational transfer of musical knowledge, reinforcing cultural identity, community cohesion, and social resilience. Traditional training based on experiential practice, improvisation, and emotional accompaniment allows communities to redefine their musical heritage in the face of the contemporary challenges of globalization and cultural homogenization. It was also evident that, although oral transmission faces threats derived from migration, urbanization, and technological changes, pedagogical and digital strategies are emerging that favor its revitalization. The Chirimía Caucana, understood as a living heritage, not only preserves historical memories but also serves as an educational and cultural resistance resource. In short, the authors reviewed agree that the effective preservation of this practice requires coordinated actions between the community, schools, and digital environments, respecting the essence of orality and strengthening its adaptation to new sociocultural dynamics.